Efficacy and safety of high-pressure balloon dilatation for primary obstructive megaureter in children: A systematic review - Aiello, Giuseppe; Morlacco, Alessandro; Bianco, Marta; Soligo, Matteo; Meneghesso, Davide; Vidal, Enrico; Rigamonti, Waifro; Dal Moro, Fabrizio (Frontiers in Urology, 2022)
Purpose. Endoscopic treatment with high-pressure balloon dilatation (HPBD) has been proposed as a feasible, safe and minimally invasive procedure for primary obstructive megaureter, but the level of evidence is still low. This systematic review aims to evaluate the efficacy and safety of HPBD and its long-term results in paediatric population. Methods. The review was conducted following the PRISMA guidelines. Systematic research of available literature in the English language from 1995 until June 2022 was conducted through EMBASE, MEDLINE, Cochrane Library and NIH Registry of Clinical Trials. For each relevant study, information was gathered regarding the study design, the inclusion/exclusion criteria, the indications for treatment, the success rate and the complications. Results. The final set included 14 studies. Median age of the patients ranged from 4 months to 7 years (full range 15 days-15 years). The indications for HPBD varied in different studies; however, most authors included patients with increasing dilation, obstructive patterns found at diuretic renogram scan, decreased renal function or symptoms. All the studies analysed reported a success rate ranging from 69 to 100% for the treatment of POM with HPBD. This approach is thought to be a definitive, less invasive, and safe treatment for this disorder that may avoid surgery in up to 77% of cases. The complication rate ranged from 0 to 50% and it was mostly infectious or associated to the stent placement or both. Conclusion. Endoscopic balloon dilation may be a safe and effective long-term option for the treatment of POM in infants and can be a definitive treatment in a considerable subset of patients. Nevertheless, the overall level of evidence for HPBD is still low and further comparative studies or randomized clinical trials are needed.